Peran Model Inkuiri dan Media Interaktif dalam Mengembangkan Kemampuan Berpikir Kritis Siswa MI: Kajian Literatur - Didit Darmawan; Yurid Citra Ayu Putri; Riska Auliatus Solichah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The development of critical thinking skills, which are essensial for problem-solving and academic achievement, remains a challenge in Madrasah Ibtidaiyah (MI), mainly due to low student engagement and differences in ability levels. This study aims to investigate the development of students’ critical thinking through an inquiry-based learning model and interactive learning media. A qualitative literature review method was employed, analyzing scientific publications from 2020 to 2024 sourced from Google Scholar, Scopus, and GARUDA. The findings indicate that inquiry-based learning increases students’ creativity, curiosity, and active participation through observation, questioning, investigation, and drawing conclusions. Meanwhile, interactive learning media increases engagement, conceptual understanding, and learning motivation through audio-visual stimuli and hands-on practice. The integration of both approaches effectively improves the cognitive, affective, and psychomotor aspects of critical thinking. However, challenges related to infrastructure limitations and teacher readiness persist, highlighting the need for inquiry-based learning integrated with interactive media, supported by teacher training and continuous evaluation.